Investigation of Concurrent Pneumococcal Meningitis in Two Children Attending the Same Day-Care Center - Rybak, Alexis; Varon, Emmanuelle; Masson, Elodie; Etchevers, Anne; Levy-Brühl, Daniel; Ouldali, Naïm; Levy, Corinne; Cohen, Robert (Frontiers in Pediatrics, 2022)
Only a few clusters of invasive pneumococcal disease have been described globally in children, and most of these cases occurred before pneumococcal vaccination implementation. Two unusual cases of pneumococcal meningitis, occurring in the same daycare center over a 3-day period, were reported. Both cerebrospinal fluid (CSF) were sent to the National reference center for pneumococci. In addition, we decided to perform a pneumococcal carriage study on all children and staff of the daycare center to analyze the pneumococcal serotypes circulating in this DCC and to discuss an antibiotic chemoprophylaxis. CSF culture was positive for pneumococcus, and serotype 25A was identified by latex agglutination. The second case had negative CSF culture, but CSF antigen test and gene amplification results were positive for Streptococcus pneumoniae. Serotype 12F was identified by using molecular biology. The absence of correlation between these strains was confirmed by multi-locus sequence typing. In the carriage study, we included 29 children (median age 1.9 years, interquartile range 1.4-2.5) and 10 adults. Among the children, 24 carried Streptococcus pneumoniae (83%). The main serotypes isolated were 23A for 6 children and 25A for 5 children; serotypes were non-typeable for 3 children. Only 1 of 10 adults tested carried Streptococcus pneumoniae (serotype 12F). Despite this temporo-spatial pattern, the cases were unrelated and not due to carriage of a particular serotype. No specific action has been taken for the other children attending this DCC, and no other case of bacterial meningitis occurred.